Inhibition of Necroptosis Rescues SAH-Induced Synaptic Impairments in Hippocampus via CREB-BDNF Pathway - Yang, Chunlei; Li, Tong; Xue, Hao; Wang, Lingxiao; Deng, Lin; Xie, Yunkai; Bai, Xuemei; Xin, Danqing; Yuan, Hongtao; Qiu, Jie; Wang, Zhen; Li, Gang (Frontiers in Neuroscience, 2019)
Subarachnoid hemorrhage (SAH) is a devastating form of stroke that leads to incurable outcomes. Increasing evidence has proved that early brain injury (EBI) contributes mostly to unfavorable outcomes after SAH. A previously unknown mechanism of regulated cell death known as necroptosis has recently been reported. Necrostatin-1 (nec-1), a specific and potent inhibitor of necroptosis, can attenuate brain impairments after SAH. However, the effect of nec-1 on the hippocampus and its neuroprotective impact on synapses after SAH is not well understood. Our present study was designed to investigate the potential effects of nec-1 administration on synapses and its relevant signal pathway in early brain injury after SAH. Nec-1 was administrated in a rat model via intraperitoneal injection after SAH. Neurobehavior scores and brain edema were detected at 24 hours after SAH occurred. The expression of the receptor-interacting proteins 1 and 3 (RIP1and3) was examined as a marker of necroptosis. We used hematoxylin and eosin staining, Nissl staining, silver staining and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) to observe the morphological changes in hippocampus. The protective effect of nec-1 on synapses was evaluated using western blotting and electron microscopy and Western blotting was used to detect the cAMP responsive element binding (CREB) protein and brain-derived neurotrophic factor (BDNF), and we used transmission electron microscopy and TUNEL to detect the protective effects of nec-1 when a specific inhibitor of CREB, known as 666-15, was used. Our results showed that in the SAH group, RIP1 and RIP3 significantly increased in the hippocampus. Additionally, injection of nec-1 alleviated brain edema and improved neurobehavior scores, compared with those in the SAH group. The damage to neurons was attenuated, and synaptic structure also improved in the Sham+nec-1 group. Furthermore, nec-1 treatment significantly enhanced the levels of phospho-CREB and BDNF compared with those in the SAH group. The protective effect of nec-1 could hindered by 666-15. Thus, nec-1 mitigated SAH-induced synaptic impairments in the hippocampus through the inhibition of necroptosis in connection with the CREB-BDNF pathway. This study may provide a new strategy for SAH patients in clinical practice.